Views and Experiences of Nurses Receiving Care as Inpatients: An Empirical Qualitative Study From Ankara - Semra Atasayar; Şenay Gül; Leyla Dinç (Nursing Open)
ABSTRACT Aim To determine the views and experiences of inpatient nurses receiving care. Background Switching from the care provider role to being a patient allows nurses to realise patients' real care expectations and to test their colleagues' care practices. Nurses' experience as inpatients is essential for understanding patients' care‐related expectations and improving care quality by reflecting on their practices. Design This qualitative study used a descriptive phenomenological design. Methods Data were collected from nine volunteer nurses between July 2018 and June 2020 in Ankara, Türkiye, through face‐to‐face interviews using semi‐structured questionnaires and audio recordings. The research data were analysed by following the descriptive phenomenological data analysis steps. The Consolidated Criteria for Reporting Qualitative Research [COREQ] checklist was used to report study findings. Results Three themes emerged from the views and experiences of nurses receiving inpatient care: care‐receiving experiences, components of good nursing care and change in perception of care. Conclusion It is important to reveal the opinions and experiences of hospitalised nurses regarding care to understand the expectations of the care recipients and to increase the quality of the care provided. The study revealed that the experiences of nurses receiving inpatient care improved their professional sensitivity and this was reflected in the quality of the nursing care they provided. Implication for Nursing Nurses can provide higher quality and humanistic care by combining their professional knowledge and skills with the increased awareness of the inpatient experience of nurses. No patient or public contribution.